Faktor-Faktor Yang Mempengaruhi Proses Ekstraksi Silika Sebagai Adsorben Untuk Pengyisihan Zat Organik Pada Air Gambut - Sarah Dwi Arini; Lita Darmayanti; Dewi Fitria (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Palm Oil Fly Ash (POFA) is one of the solid wastes from the combustion of shells and palm fiber in the boiler. It is potential as an adsorbent because of its high silica content. Adsorption is one method that has the potential to remove color and organic matter substances in peat water. The purpose of this research is to study the effect of the ratio raw materials to solvents to the production of silica extracted from POFA and to determine the efficiency removal of Fe in peat water. The results of this study show the colors, organic substances and Fe in 1830 Pt/Co, 437,8 mg/l, and 0,07 mg/l. Keywords: Palm oil fly ash, silica, extraction, ratio of raw material to solvent, processing time, peat water, adsorption